COUNSELING SERVICES: IMPROVE CLIENTS' EMOTIONS AND SPIRITUALITY ACCORDING TO THE ISLAMIC PERSPECTIVE - Nurshahira Ibrahim,; Rasyad Afif Ibrahim,; Nurul Hidayah Che Hassan,; Mohd Lokman Sapiee,; Abu Bakar Jaafar,; Wan Azmi Wan Ahmad,; Md Hamzaimi Azrol Md. Baharudin,; Ramlan Mustapha,; Muhammad Muzzakkir Othman, (Journal of Islamic, Social, Economics and Development, 2024)
This study was conducted to assess the relationship between emotional intelligence (self-awareness and self-motivation) and spiritual intelligence at one of the counseling agencies in Malaysia. A total of 111 counseling clients responded to the questionnaire. SmartPLS analysis is used to test the hypothesis of the study. The results revealed some important findings: First, there is a positive but insignificant relationship between self-awareness and spiritual intelligence. Second, there is a positive and significant relationship between self-motivation and spiritual intelligence. This study confirms that emotional intelligence is an important variable for building spiritual intelligence. The findings of this study can be used can help practitioners understand the diversity of perspectives on the construction of emotional intelligence that can guide counseling sessions to help achieve and maintain the emotional well-being of the counseling clients.